Development of TCM herb and anti-hypertensive drug interaction database - Yeow, Melissa Wei Bao (2014)
Traditional Chinese Medicine (TCM) is a very popular used form of Complementary and Alternative Medicine (CAM) in Singapore. Given the high rate of hypertension in Singapore, it is not surprising that TCM and anti-hypertensive drugs are used concomitantly by the general public. However, both the general public and healthcare professionals (HCPs) are poorly informed about TCM herb-drug interactions, and lack access to information about them.